Between-strain differences in hypothermic response in mice after intranasal administration of PtO nanoparticles - D. V. Petrovskii; A. V. Romashchenko; S. Yu. Troitskii; M. P. Moshkin (Вавиловский журнал генетики и селекции)
Air pollution by particulate matter (PM) has been associated with cardiopulmonary morbidity and mortality in many recent epidemiological studies. It has been shown that transition metal compounds, well- known toxic components of PM, are able to induce hypothermia following whole-body inhalation exposure. Low temperature appears to protect tissue against toxic effects of PM metal compounds in vivo and in vitro. To study the role of soluble and insoluble irritants in the induction of the hypothermic response, we analyzed the decrease in mouse body temperature (Δtbody) after intranasal administration of PtO nanoparticles or a K2[PtCl 4] solution. Between-strain differences in Δtbody after intranasal administration of the irritants were evaluated using 6 inbred (BALB/cJ, C57BL/6J, AKR/OlaHsd, DBA/2JRccHsd, C3H/HeNHsd, and SJL/J) and 2 outbred mouse strains (SCID and CD1). BALB/cJ and SCID mice showed the most pronounced effect of intranasal administration of the xenobiotic on tbody. Thus, tbody was significantly lower after nasal administration the PtO nanoparticles than after administration of the K2[PtCl 4] solution. To study the mechanism of this decrease, we compared the respective values for Δtbody following intranasal, intravenous and peroral administration of PtO nanoparticles in Balb/c mice. Neither intravenous nor peroral administration had any effect on mouse body temperature. This fact together with data on the dynamics of the decrease in mouse body temperature following intranasal administration of PtO nanoparticles (max Δtbody ~ 80–100 min) allowed us to assume that this process is under nervous regulation. The correlation found between our data and some well-known phenotypic characteristics (phenome.jax.org) of the mouse strains used confirms this hypothesis.